Modeling historical fecal coliform loadings to large European rivers and resulting in-stream concentrations. (January 2015) - Reder, Klara; Flörke, Martina; Alcamo, Joseph
Abstract: Information on fecal coliform (FC) concentrations in European rivers is scarce. The objective of this study was to identify hotspots of water pollution in Europe and provide information on the different FC sources and their contributions to the loads that lead to concentrations in rivers. Model simulations were carried-out with the large-scale water quality model WorldQual to assess the calculated loads regarding to its associated sources and to further estimate the related in-stream concentration. For the year 1995, model results indicated that FC loadings were higher in central Europe with 500 to above 2000 10 10 cfu km −2 a −1 than in northern and eastern Europe where loadings ranged between 0 and 200 10 10 cfu km −2 a −1 . Major sources of FC loadings are domestic sewage, followed by scattered settlements (private treatment), urban surface runoff and manure application. Concentrations showed similar regional patterns as loadings, with high concentrations in central Europe and low concentrations in northern and eastern Europe. Highlights: We model fecal coliform loadings and in-stream concentrations in European rivers. The domestic sector is the main contributor to fecal coliform loadings. The regional patterns of loadings and in-stream concentrations are similar. Hotspots of fecal coliform in-stream concentrations are located in central Europe.